Laboratory Studies for The Development of a Demulsifier in Handling Production Fluid Emulsions in The â€œSRGâ€ Field - KRT Nur Suhascaryo; Halwin Ariandi Siregar; Ridwan Ridwan (Testing Center for Oil and Gas LEMIGAS, 2022)
The â€œSRGâ€ Oil Field is located in the South Sumatra basin, and the oil produced is classified as heavy oil and generally water-oil emulsion occurs. As a result of the formation of this emulsion which will cause corrosion of equipment in the field. The samples that have been taken in the field are then investigated in the laboratory of PT Farca Risa Sejahtera. First, perform BS&W testing on GS-belimbing and GS-11 oil samples to determine the water content and deposits present in the oil. The second is to determine the ratio of the amount of oil and formation water to be used in subsequent tests. The third selection of demulsifiers for formulation materials is based on the ability of water drop, clear water and interface. The four demulsifier formulations combine the demulsifiers that pass the selection into 5 formulas with the hope of uniting the advantages and covering each otherâ€™s shortcomings of each demulsifier that passes the selection. The fifth test is overtreated to determine the appropriate dose for the use of a predetermined demulsifier formula. Emulsion sample testing was also carried out on CGS oil samples (GS-belimbing oil and GS-11) plus the oil present in the pits. The six BS&W tests after using the new formula. GSbelimbing has a production rate of Â±22,000 BFPD with a water cut value obtained from the separator test in the field and validated by the BS&W test in the laboratory of Â±92%, the value of oil production in GS Belimbing is Â±1760 BOPD. While the GS-11 has a production rate of Â±33,000 BFPD with a water cut value of Â±91%, the value of oil production in GS 11 is Â±2970 BOPD. While the CGS has a fluid production rate of Â± 58,000 BFPD with a water cut of Â± 90%, the value of oil production at the CGS is Â± 5800 BOPD. Formula code H5 with a composition of 10% (F13; water drop) plus 10% (1030; interface) and 80% (F-16; clear water) which was selected for GS-belimbing. The formula with code A1 which has a composition of 80% F-8 plus 10% 1030 and 10% F-16 was chosen for the GS-11. For the CGS, the S5 formula is 10% (F-16 clear water) plus 10% (1030; interface) and 80% (F-8; water drop). The results of the BS&W test after the new formula showed that there was no water in the oil in the centrifuge tube and it was stated that the BS&W value was close to 0%. There are 3 demulsifier products from the formulation, namely HAS-1 for GS-belimbing, HAS-2 for GS-11, and HAS-3 for CGS plus pit. The amount of HAS-3 demulsifier that needs to be injected into the CGS is 7.31 gallons per day (GPD). The number of HAS-1 demulsifier injected into GS Belimbing was 2.22 GPD, while the number of HAS-2 demulsifier injected into GS-11 was 3.74 GPD